New locations of species of the genus Astragalus L. in Kazakhstan - Пережогин, Ю.В.; Бородулина, О.В.; Ерохин, Н.Г.; Кубентаев, С.А. (Fundamental and Experimental Biology, 2023)
During the revision of the herbarium collections of the Institute of Plant and Animal Ecology of the Ural Branch of the Russian Academy of Sciences (SVER) and the Lomonosov Moscow State University (MW), 17 species of the genus Astragalus were identified that had not previously been noted for certain floristic regions (FR) of Kazakhstan: the South Ustyurt FR – 12 species (Astragalus ammophilus, A. ankylotus, A. arcuatus, A. brachypus, A. campylorhynchus, A. commixtus, A. corrugatus, A. filicaulis, A. flexus, A. oxyglottis, A. stalinsky and A. tribuloides), Turgai FR – 3 species (Astragalus ammodytes, A. lehmannianus and A. paucijugus) and Embensky FR – 1 species (Astragalus kustanaicus). These findings significantly expand the existing understanding of the distribution of these species in the flora of Kazakhstan.